Transient response of offshore wind turbines on monopiles in sand: role of cyclic hydro–mechanical soil behaviour. (March 2017) - Corciulo, Simone; Zanoli, Omar; Pisanò, Federico
Abstract: Offshore wind turbines (OWTs) in relatively shallow waters are most often founded on monopile foundations, whose design is extremely relevant to the OWT dynamic performance under environmental loading. In this study, 3D finite element (FE) modelling is applied to the dynamic analysis of OWTs and proposed as a valuable support to current design practice. FE results are presented about the interplay of cyclic soil behaviour and hydro-mechanical coupling in determining the OWT natural frequency: in dilative sands, the natural frequency seems not to decrease monotonically at increasing loading amplitude, while slight influence of soil permeability is found.